2014
DOI: 10.4049/jimmunol.1301034
|View full text |Cite
|
Sign up to set email alerts
|

Oral Combined Therapy with Probiotics and Alloantigen Induces B Cell–Dependent Long-Lasting Specific Tolerance

Abstract: Allogeneic hematopietic stem cell transplantation (aHSCT) is widely used for the treatment of hematologic malignancies. Although aHSCT provides a good response against the malignant cells (graft-versus-leukemia [GVL]), it also leads to the development of graft-versus-host disease (GVHD), a severe disease with high mortality and morbidity rates. Therapy for GVHD is commonly based on nonspecific immunosupression of the transplanted recipient, resulting in the concomitant inhibition of the GVL effect. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 58 publications
4
16
0
5
Order By: Relevance
“…In this way, when Treg cells are depleted early after the transplantation, the GVHD protection is abolished, showing Treg induction within the host right after transplantation. These specific suppressor effects are compatible with the antigen-specific suppression previously observed with Treg cells [97,98]. (Figure 3).…”
Section: Role Of Regulatory Neutrophils In Gvhd Protectionsupporting
confidence: 89%
“…In this way, when Treg cells are depleted early after the transplantation, the GVHD protection is abolished, showing Treg induction within the host right after transplantation. These specific suppressor effects are compatible with the antigen-specific suppression previously observed with Treg cells [97,98]. (Figure 3).…”
Section: Role Of Regulatory Neutrophils In Gvhd Protectionsupporting
confidence: 89%
“…A recent study showed that probiotics played an important role in B-celldependent specific tolerance, in an animal model. 5 Clearly, there is much more to explore and learn about the intestinal microbiota, and their implications for human health.…”
mentioning
confidence: 99%
“…Probiotics also have an effect on B regs . Mercadante et al (102) have shown that L. lactis can promote the generation of IL-10-producing B cells that mediate tolerance in a model of graft-versus-host disease. Clostridium butyricum, when given in combination with specific immunotherapy, significantly increases the frequency of IL-10 + B cells in both mice and humans (103,104).…”
Section: Emergence Of Microbiome-directed Therapies For Eae and Msmentioning
confidence: 99%